Advances in water and wastewater treatment technology molecular technology, nutrient removal, sludge reduction and environmental health - Matsuo, Tomonori (Elsevier, 2001)
This book is the result of the international symposium, "Establishment and Evaluation of Advanced Water Treatment Technology Systems Using Functions of Complex Microbial Community", organized in 2000 at the University of Tokyo. The volume presents the most recent progress in application of microbial community analysis, health-related microorganisms management, nutrient removal, waste sludge minimization and materials recovery, and water management in tropical countries. Included in this work are the following major topics in wastewater treatment: application of various innovative techniques of molecular biology such as FISH, DGGE to microbial community analysis of various types of wastewater treatment; microbial aspect of biological removal of nitrogen and phosphorus; emission of nitrous oxide during nitrogen transformation; reduction of sludge production in the wastewater treatment process using membrane and material recovery of biopolymer and cell of photosynthetic bacteria. Health-related microbiology in water supply and water management using recent innovative molecular biological tools is presented and health risk management is discussed. The practical application of wastewater treatment in developing countries, especially tropical countries is also reviewed. Researchers in the field of environmental engineering and applied microbiology, and practical engineers who wish to learn the most recent progress in the microbiological aspect of water and wastewater management, will find this book a useful tool.
Keywords: Water -- Purification.; Water -- Purification -- Biological treatment.; Sewage -- Purification.; Sewage -- Purification -- Biological treatment.; Sewage -- Purification -- Nutrient removal.; elektronické knihy; electronic books